PROCESS OF THE COMMUNITY ECONOMY DEVELOPMENT BASED ON SOCIAL AND CULTURAL CAPITALS OF NORTHEASTERN REGIONS’ COMMUNITIES - Kaewla, Wasana (International Journal of Psychosocial Rehabilitation, 2020)
The purposes research were to study background of social and cultural capital of the Kui ethnic group community context, to study the system and innovation, and to develop process of the economic development of the community, based on the social and cultural capital of the community in the lower northeastern regions. Qualitative research tools were used semi-structure interview form. Data collected from in-depth interview, focus group discussion,99 key informants was specified characteristics. Qualitative data were analyzed by using content analysis, verified with triangulation method, rigorous and credibility was concerned. Whereas preliminary qualitative research results was critiques 10 experts by group dialogue. After receiving comments and public hearing was shared idea. Researcher constructed the significantly thematic of model was verified. Results shown that 1) economic development process of the Kui communities, that emphasized on social and cultural capital in community. Issues of community economic development process, based on the social and cultural capital, community such as belief, faith, awareness. Community values and symbols of belief which are local wisdom that passed down from the community, which considered an intangible culture. Processing, of the system development and innovation based on the TERMS. concept and LIST. model. According to concept: consisted of natural resource capitals is necessary for the prosperity and sustainability of subsistence economic development and the exchange of traditional products. Later, modern knowledge applied by using appropriate technology, with community leaders as leaders in development, while the government implement on development policies and roles in development participation. Leaders as the primary, kept traditions and rituals are preserved income. It is called ritual based community economy. Operated the economic development process maintain the identity of the community, develop themselves, transition into the creative economy until became community’s tourism bringing income produced revenue-generating products.